Caregivers’ understanding of childhood influenza vaccination during the epidemic in China. A mixed-methods study - Han, Kaiyi; Hou, Zhiyuan; Tu, Shiyi; Wang, Qian; Hu, Simeng; Xing, Yuting; Du, Jing; Zang, Shujie; Chantler, Tracey; Larson, Heidi (Frontiers in Public Health, 2023)
Introduction: Influenza vaccination uptake among young children has been poor in China, but it is unclear how it changed during the COVID-19. This study aimed to investigate the uptake status and reasons of childhood influenza vaccination during the pandemic in China. Methods: A mixed-methods study combining a questionnaire survey and semi-structured interviews was conducted in Anhui, Shaanxi, and Guangdong provinces between September and November 2021. 2081 caregivers completed the valid questionnaire. 38 caregivers participated in interviews, and data were analyzed thematically, using deductive and inductive coding. Results: A total of 2081 caregivers completed the valid questionnaire, and 38 caregivers participated in interviews. Among the caregivers, a total of 1796 were in the age group for high-risk groups in the 2019-2020 flu season, and 46.10 % reported that their children received influenza vaccination in the 2019-2020 flu season; 43.63% said that they vaccinated their children against influenza in the 2020-2021 flu season. Many caregivers indicated that the adoption of nonpharmacologic interventions (NPIs) during COVID-19 reduced the risk of influenza infection for children. Most caregivers consider the severity of influenza to be low, and some confused the common cold with influenza. Meanwhile, some caregivers lack confidence in the vaccine’s effectiveness and importance. They thought that vaccines are not effective in preventing the constantly mutating virus. Despite clear perceptions about the severity of influenza and the effectiveness of the vaccine, we found that most caregivers did not receive any relevant medical information, and the communication about vaccines between caregivers and professional information sources, such as healthcare workers, is inadequate. Hence, caregivers have no scientific evidence to back up their perceptions. In terms of access to vaccination service, caregivers reported conflicts between time of vaccination service and their schedule, and the need for vaccine prices to be reduced. Discussion: Targeted interventions are needed to address caregivers’ lack of risk perception on influenza during COVID-19 and promote communication between caregivers and professional information sources. Extending vaccination service hours and increasing the number of vaccine clinics close to residential areas and expansion of financing sources for self-paid vaccination could facilitate the access to influenza vaccination service.